2020
DOI: 10.1111/obr.13078
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace with overweight and obesity: A systematic review and meta‐analysis of epidemiological studies up to 2020

Abstract: Several reviews have been conducted to assess the association between greenspace and overweight or obesity, but the conclusions were inconsistent. However, an updated comprehensive review and meta-analysis is warranted, because several high-quality papers have been published more recently. The objectives of this study are to systematically and quantitatively assess the evidence for a link between greenspace with overweight/obesity and to make specific recommendations for further research. We searched three Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 91 publications
2
55
2
Order By: Relevance
“…Several studies considered race/ethnicity effects for pregnant woman [ 56 , 57 ] and school children [ 28 ]. They note that the potential built environment reflecting cultural preferences has plausible implications for health behaviour and outcomes [ 58 ]. Therefore, further research on children should include more comprehensive and multidimensional metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies considered race/ethnicity effects for pregnant woman [ 56 , 57 ] and school children [ 28 ]. They note that the potential built environment reflecting cultural preferences has plausible implications for health behaviour and outcomes [ 58 ]. Therefore, further research on children should include more comprehensive and multidimensional metrics.…”
Section: Discussionmentioning
confidence: 99%
“…However, research results on the relationship between the proximity of green spaces and BMI are not always consistent. 91 Luo et al 91 reviewed epidemiological studies on green spaces and overweight/obesity published before January 2020 and conducted a meta-analysis on 57 studies in seven countries. They found that 55% of the studies reviewed reported an association between green space and lower odds of overweight/obesity in overall or subpopulations.…”
Section: Reduced Green Spacementioning
confidence: 99%
“…In this respect, residential green and blue spaces were found to regulate ecosystem services, improve air quality, reduce heat island effects, and diminish noise pollution [ 3 , 4 ]. Meanwhile, they can also promote overall public health by increasing physical activity, improving self-perceived health, and lowering the incidence of respiratory diseases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%